The Origin of Selective Adsorption of CO2 on Merlinoite Zeolites. Issue 8 (16th December 2020) - Choi, Hyun June; Jo, Donghui; Min, Jung Gi; Hong, Suk Bong
Abstract: The CO2 adsorption behavior at 25–75 °C and 0–1.0 bar of various alkali cation‐exchanged forms of merlinoite (framework type MER) zeolites with Si/Al=2.3 and 3.8 is described. The adsorption isotherms at 25 °C on the Na +, K +, Rb +, and Cs + forms of MER zeolite with Si/Al=2.3 are characterized by a clear step, the CO2 pressure of which differs notably according to the type of their extraframework cations. Structural analysis shows that CO2 adsorption on the former three zeolites includes the relocation of gating cations with high site occupancy and the remarkable concomitant structural breathing. We define this unusual adsorption phenomenon as a cooperative cation gating‐breathing mechanism. The overall results suggest that the actual mechanism of selective CO2 adsorption on intermediate‐silica small‐pore zeolites can change from cation gating to cooperative cation gating‐breathing to breathing, depending on a combination of their topological and compositional flexibilities. Abstract : The dominant mechanism of selective CO2 adsorption on intermediate‐silica small‐pore zeolites can change from cation gating to cooperative cation gating‐breathing to breathing, depending on both the framework Si/Al ratio (or alkali cation concentration) and extraframework cation type and thus location, as well as on the framework topology.